Weak Participation and Ideological Exemption: The Latest Stage of EIA Simplification in Brazil?. Issue 3 (4th May 2023) - Fonseca, Alberto
ABSTRACT: Developers' concerns over the costs and delays of environmental impact assessment (EIA) have increasingly been driving 'simplification' solutions and reforms. This letter critically reviews the evolution of EIA simplification in Brazil. More specifically, it (1) sets out to describe the main stages of EIA simplification in Brazil, and (2) calls for conceptually clear and evidence-based simplification reforms. I argue that the first simplification efforts in Brazil mirrored an attempt to bring procedural proportionality to EIA. But simplification gradually became a more nuanced phenomenon reflecting a variety of streamlining, digitalization, and decentralization strategies. However, the many simplification efforts do not seem to be affecting developers' predominant perception about EIA ineffectiveness. Brazil may be witnessing a more radical stage of EIA simplification, in which 'simplicity' is pursued through weak public participation and the exemption of specific economic sectors of the Brazilian economy from EIA. Without conceptually clear and evidence-based simplification reforms, debates over EIA effectiveness are likely to be influenced by simplistic win-win narratives, and Brazil's increasingly fragile environment is likely to get worse.